Fatherhood in the Borderlands : A Daughter's Slow Approach. - Perez, Domino Renee (Austin : University of Texas Press, 2022)
As a young girl growing up in Houston, Texas, in the 1980s, Domino Perez spent her free time either devouring books or watching films--and thinking, always thinking, about the media she consumed. The meaningful connections between these media and how we learn form the basis of Perez's "slow" research approach to race, class, and gender in the borderlands. Part cultural history, part literary criticism, part memoir, Fatherhood in the Borderlands takes an incisive look at the value of creative inquiry while it examines the nuanced portrayal of Mexican American fathers in literature and film. Perez reveals a shifting tension in the literal and figurative borderlands of popular narratives and shows how form, genre, and subject work to determine the roles Mexican American fathers are allowed to occupy. She also calls our attention to the cultural landscape that has allowed such a racialized representation of Mexican American fathers to continue, unopposed, for so many years. Fatherhood in the Borderlands brings readers right to the intersection of the white cultural mainstream in the United States and Mexican American cultural productions, carefully considering the legibility and illegibility of Brown fathers in contemporary media.
Frontmatter -- CONTENTS -- Preface THE SLOW LOWDOWN -- Introduction A SLOW APPROACH TO FATHERS AND OTHER FICTIONS -- PART I Sourcing Authority -- Introduction -- Film ANCIANOS NOT ABUELOS Making Space and Mediating Male Power -- Personal narrative "NO, I AM YOUR FATHER" -- Literature FATHERS AND RACIALIZED MASCULINITIES IN LUIS ALBERTO URREA'S IN SEARCH OF SNOW -- PART II Instrumentalizing Indigeneity -- Introduction -- Personal narrative NOBODY EVER SAID WE WERE AZTECS -- Film FATHERHOOD, CHICANISMO, AND THE CULTURAL POLITICS OF HEALING IN LA MISSION -- Lterature NEW TRIBALISM AND CHICANA/O INDIGENEITY IN THE WORK OF GLORIA ANZALDÚA -- PART III Fantasmas and Fronteras -- Introduction -- Literature FATHERS, SONS, AND OTHER (SHORT) FICTIONS -- Film META AND MUTANT FATHERS -- Personal narrative FAMILY FICTIONS AND OTHER LIES ABOUT THE TRUTH -- Conclusion FATHERS AND FUTURITY -- PARTING SHOT -- ACKNOWLEDGMENTS -- NOTES -- WORKS CITED AND CONSULTED -- INDEX
JSTOR
Keywords: Perez, Domino Renee, -- 1967-; Mexican Americans in literature -- Case studies; Mexican Americans in motion pictures -- Case studies; Fathers in literature -- Case studies; Fathers in motion pictures -- Case studies; Fatherhood in literature -- Case studies; Fatherhood in motion pictures -- Case studies; Américains d'origine mexicaine dans la littérature -- Études de cas; Américains d'origine mexicaine au cinéma -- Études de cas; Pères dans la littérature -- Études de cas; Pères au cinéma -- Études de cas; Paternité dans la littérature -- Études de cas; Paternité au cinéma -- Études de cas; SOCIAL SCIENCE / General; Fatherhood in literature; Fatherhood in motion pictures; Fathers in literature; Fathers in motion pictures; Mexican Americans in literature; Mexican Americans in motion pictures; Electronic books; Case studies